TINJAUAN KRIMINOLOGI TERHADAP FAKTOR PENYEBAB PELANGGARAN RAMBU LALULINTAS OLEH PENGENDARA SEPEDA MOTOR DI KOTA SEMARANG - Yesi Putri Utami (Jurnal Ilmiah Dinamika Hukum, 2018)
The purpose of this study are (1) to analyze the factors that cause violations of traffic signs by motorcycle riders in the city of Semarang. (2) To analyze criminological studies of violations of traffic signs by motorcyclists in Semarang City. The approach method is done juridically sociologically, specification descriptively using primary data and secondary data, through interviews and literature, then analyzed qualitatively. The results of the discussion show that (1) the factors that cause violations of traffic signs by motorcyclists in Semarang City are human factors, among others, the driver's indiscipline, the intent of the driver and the pretense of the driver. (2) Criminological study of violations of traffic signs by motorcycle riders in the city of Semarang, namely the presence of awareness, discipline, public interest in having a vehicle, incompetence factor